Administration of Psoralea corylifolia L. (Buguzhi) during pregnancy causes mild liver injury in mouse mothers and weaned offspring - Chenyue Liu; Jingzhuo Tian; Yan Yi; Chunying Li; Yong Zhao; Jiayin Han; Lianmei Wang; Suyan Liu; Yushi Zhang; Chen Pan; Shasha Qin; Jing Meng; et al. (Science of Traditional Chinese Medicine)
Abstract. Background. Psoralea corylifolia L. (Buguzhi, BGZ), known for its efficacy in supporting pregnancy and preventing miscarriage, has been used in China for over 1000 years. Recently, BGZ has been identified as a potential cause of drug-induced liver injury. However, its safety during pregnancy remains unclear, which significantly hinders its routine clinical application. Objective. To investigate the effects of BGZ administration during pregnancy on the liver of mouse mothers and their weaned 21-day-old offspring. Methods. Mice were orally administered BGZ at doses of 2.5 and 10 g/kg during pregnancy, with BGZ withdrawal during the lactation period. Liver histopathology (hematoxylin-eosin staining), biochemical analysis, and evaluation of liver bile acid metabolism were performed after the lactation period. Results. BGZ administration at doses of 2.5 and 10 g/kg during pregnancy, followed by withdrawal during the lactation period, caused mild liver damage in both mothers and their 21-day-old offspring. Serum total bile acid (TBA) levels were elevated compared with those in the control group. Additionally, changes were observed in the levels and proportions of various bile acids (BAs) in the liver, suggesting mild effects on BA metabolism. Conclusion. BGZ administration during pregnancy caused mild liver damage and increased serum TBA levels in both mouse mothers and their 21-day-old offspring. This phenomenon may be associated with imbalanced BA metabolism in the liver. Based on the present study and the limited toxicological research on BGZ, pregnant women should avoid prolonged use of BGZ. If BGZ is administered during pregnancy, serum TBA levels should be monitored, and if elevated, BGZ should be discontinued.